Comorbid Trajectories of Postpartum Depression and PTSD among Mothers with Childhood Trauma History: Course, Predictors, Processes and Child Adjustment - Oh, Wonjung (J Affect Disord, 2016)
BACKGROUND: Both postpartum depression and posttraumatic stress disorder (PTSD) have been identified as unique risk factors for poor maternal psychopathology. Little is known, however, regarding the longitudinal processes of co-occurring depression and PTSD among mothers with childhood adversity. The present study addressed this research gap by examining co-occurring postpartum depression and PTSD trajectories among mothers with childhood trauma history. METHODS: 177 mothers with childhood trauma history reported depression and PTSD symptoms at 4, 6, 12, 15 and 18 months postpartum, as well as individual (shame, posttraumatic cognitions, dissociation) and contextual (social support, childhood and postpartum trauma experiences) factors. RESULTS: Growth mixture modeling (GMM) identified three comorbid change patterns: The Resilient group (64%) showed the lowest levels of depression and PTSD that remained stable over time; the Vulnerable group (23%) displayed moderately high levels of comorbid depression and PTSD; and the Chronic High-Risk group (14%) showed the highest level of comorbid depression and PTSD. Further, a path model revealed that postpartum dissociation, negative posttraumatic cognitions, shame, as well as social support, and childhood and postpartum trauma experiences differentiated membership in the Chronic High-Risk and Vulnerable. Finally, we found that children of mothers in the Vulnerable group were reported as having more externalizing and total problem behaviors. LIMITATIONS: Generalizability is limited given sample of mothers with childhood trauma history and demographic risk. CONCLUSIONS: The results highlight the strong comorbidity of postpartum depression and PTSD among mothers with childhood trauma history, and also emphasize its aversive impact on the offspring.